Pemanfaatan Bunga Telang Sebagai Upaya Anti Oksidan Pada Remaja Di Lingkungan SMK Patria Gading Rejo - Afikirtiani, Winda; Sugiarto; Mustopa; Simanjuntak, Betty; Larombia, Sufiana; Joko Susilo, Dwi; Endi Fernanda, Fitra; Sa'idah, Siti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Telang flower (Clitoria Ternatea L.) is a type of flowering plant from the legume tribe with a purplish color that contains anthocyanin compounds as a source of antioxidants. Antioxidants play an important role in protecting the body from oxidative damage caused by free radicals that can trigger various degenerative diseases. One form of telang flower utilization is processed as a health drink. However, information regarding the utilization of telang flowers as a health drink is still very rarely known by the public, especially in teenagers. Objective: The purpose of this service was to provide knowledge and skills to adolescents in the environment of SMK Patria Gading Rejo regarding the benefits of telang flowers as antioxidants and the correct way of processing. Method: This public service was conducted by Desember 2024 with a lecture method using Project Still media and direct demonstrations to teenagers in the environment of SMK Patria Gading Rejo.  Result: The results of this activity can increase participants understanding of the benefits of telang flower tea as an anti oxidant with an average pre test score of 35 and an average post test score of 80.5. In addition, participants can directly demonstrate how to make telang flower tea properly and correctly with a total percentage reaching 65% and participants who demonstrate less well and correctly only reach 35%. Conclusion: There is an understanding of adolescents at SMK Patria Gading Rejo about the process of making and business opportunities for telang flower tea.